Villes et architectures de Palestine - Vilan, Luc; Roujon, Yves (Presses de l’Ifpo, 2026)
For many people, Hebron, Bethlehem and Nablus bring to mind archaeology, biblical history, cultural issues and the contemporary geopolitical situation, but rarely the architecture or the shape of the towns. This book reveals a twofold discovery: that of a remarkable architectural and urban heritage and that of a particular type of dwelling, the hosh (the large Palestinian house), which clearly distinguishes Palestinian towns and villages from other towns in the Middle East.This book is the result of a meticulous survey of buildings and urban spaces. While drawings can claim a certain objectivity through the very technique of representation, the point of view of the authors cannot fail to influence the written descriptions and explanations. It is perhaps the particular quality of this book that it leaves it up to the reader to interpret the collection of graphical documents providing a panorama of these three towns at different scales, while at the same time providing text with possible keys to interpretation.This survey is thus of major importance. It reveals the nature of the urban spaces, the monuments and buildings specific to each city, as well as showing the common features of their historic architecture.